Eksplorasi Nilai Ekoteologi Islam Dalam Elemen Al-Qur’an Dan Hadis Kurikulum Pendidikan Agama Islam Fase D - Akbar Muharom; Muhammad Hazballoh; M. Musthofa Asy’ari (Program Pascasarjana IIQ Jakarta, 2025)
This study aims to explore and analyze Islamic eco-theological values found in the elements of the Qur'an and Hadith within the Islamic Religious Education Phase D curriculum, to foster ecological awareness among students. The research uses a qualitative approach with a literature study through content analysis of the Islamic religious education curriculum guidebook and textbooks for grades VII, VIII, and IX. The data were analyzed through the identification of material units, categorization of eco-theological values, and interpretation of their theological and pedagogical meanings. The results showed that there were three main Islamic eco-theological values represented in the elements of the Qur'an and Hadith, namely the values of tauhid, amanah, and khalifah fil ardh. The value of tauhid emphasizes the spiritual awareness that nature is a sign of Allah's power, which must be respected. The value of amanah emphasizes human responsibility in protecting and utilizing the environment proportionally. The value of khalifah fil ardh places humans as stewards of the earth who are obliged to prevent damage and maintain the sustainability of the ecosystem. These findings indicate that the PAI Phase D curriculum has provided a conceptual foundation for Islamic-based ecological education but still requires re-actualization through cross-element integration and learning innovation. This study emphasizes the urgency of strengthening eco-theological education in schools as part of character building that cares for the environment.